INTEGRATION AND RELATIONALIZATION BETWEEN THE FACT OF REVELATION AND THE FACT OF SCIENCE (A STUDY OF THE MIRACLES OF THE QUR'AN) - Inda, Marlinda; Juswandi, Juswandi; Musa, Muh. Radiyal (Ma'had Aly As'adiyah Sengkang, 2024)
This article examines the integration and relationalization between the facts of revelation and scientific facts, focusing on the miracles of the Qur'an. The Qur'an, as the holy book of Islam, is often cited as containing verses with scientific knowledge that has only been revealed by modern science. This research aims to understand how verses of the Qur'an that are considered to contain scientific miracles can be explained and understood in the context of contemporary science. Through literature review and comparative analysis methods, this study finds that there are many verses in the Qur'an that implicitly and explicitly align with modern scientific discoveries in fields such as astronomy, embryology, and geology. The results show that the integration and relationalization between the facts of revelation and scientific facts not only strengthen spiritual beliefs but also enrich scientific understanding and open constructive dialogue between religion and science.